THE CONCEPT OF BLOOD PURIFICATION IN THE CONTEXT OF SCIENTIFIC RACISM IN THE 18TH CENTURY - Campos Rivas, Carlos Federico (2017)
This article aims to analyze the presence of the concept of blood cleansing in scientific racism, by drawing equivalences and analogies with the caste discourse that prevailed in 18th century Spanish America. With the study of this conjuncture it is intended to demonstrate the existence of a taxonomical dialogue and mutual influence between the fronts of the scientific racism and the traditional conception of caste in the colonial society. Through the study of the main authors and printed works of the scientific racism paradigm, it is intended to discover the genealogical conception of the posterity of mixed lineages, reviewing its compatibility with the main theories of monogenism and polygenism, and demonstrating the survival of traditional concepts about blood and temperament. This work contributes to explain how Spanish America was taken as a sort of social laboratory for the cause of scientific racism, providing its long-lived experience in the theme of miscegenation.